Small amplitude electron acoustic solitary waves in a magnetized superthermal plasma - Devanandhan, S.; Singh, S. V.; Lakhina, G. S.; Bharuthram, R. (My University, 2015)
The propagation of electron acoustic solitary waves in a magnetized plasma consisting of fluid cold electrons, electron beam and superthermal hot electrons (obeying kappa velocity distribution function) and ion is investigated in a small amplitude limit using reductive perturbation theory. The Korteweg–de-Vries–Zakharov–Kuznetsov (KdV–ZK) equation governing the dynamics of electron acoustic solitary waves is derived. The solution of the KdV–ZK equation predicts the existence of negative potential solitary structures. The new results are: (1) increase of either the beam speed or temperature of beam electrons tends to reduce both the amplitude and width of the electron acoustic solitons, (2) the inclusion of beam speed and temperature pushes the allowed Mach number regime upwards and (3) the soliton width maximizes at certain angle of propagation (αm) and then decreases for α>αm. In addition, increasing the superthermality of the hot electrons also results in reduction of soliton amplitude and width. For auroral plasma parameters observed by Viking, the obliquely propagating electron-acoustic solitary waves have electric field amplitudes in the range (7.8–45) mV/m and pulse widths (0.29–0.44) ms. The Fourier transform of these electron acoustic solitons would result in a broadband frequency spectra with peaks near 2.3–3.5 kHz, thus providing a possible explanation of the broadband electrostatic noise observed during the Burst a.
Keywords: Nonlinear waves; Space plasmas; Electron-acoustic solitons; Solitary waves